Unbounded solution of characteristic singular integral equation using differential transform method - Mahiub, Mohammad Abdulkawi (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this paper, The differential transform method is extended to solve the Cauchy type singular integral equation of the first kind. Unbounded solution of the Cauchy type singular Integral equation is discussed. Numerical results are shown to illustrate the efficiency and accuracy of the present solution.